2009
DOI: 10.1200/jco.2008.18.7229
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Infiltrating FOXP3+ T Regulatory Cells Show Strong Prognostic Significance in Colorectal Cancer

Abstract: FOXP3(+) Treg density in normal and tumor tissue had stronger prognostic significance in colorectal cancer compared with CD8(+) and CD45RO(+) lymphocytes. The finding of improved survival associated with a high density of tumor-infiltrating FOXP3(+) Tregs in colorectal cancer contrasts with several other solid cancer types. The inclusion of FOXP3(+) Treg density may help to improve the prognostication of early-stage colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

65
708
8
8

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 907 publications
(789 citation statements)
references
References 37 publications
65
708
8
8
Order By: Relevance
“…Another explanation to the favourable impact of PD-L1 expression, contradicting results from other types of solid cancer, is that the immune cell infiltration in CRC might be associated with paradoxical features due to the microbiota of the colon. For example, in contrast with the majority of human cancers, the infiltration of FoxP3 + immune cells in CRC has in the herein investigated cohort 14 and others, 30 , 31 been found to be an auspicious prognostic factor. It should however be pointed out that the herein described inter-correlations between different subsets of immune cells merely reflect their co-localization in selected tumour regions.…”
Section: Discussionmentioning
confidence: 59%
“…Another explanation to the favourable impact of PD-L1 expression, contradicting results from other types of solid cancer, is that the immune cell infiltration in CRC might be associated with paradoxical features due to the microbiota of the colon. For example, in contrast with the majority of human cancers, the infiltration of FoxP3 + immune cells in CRC has in the herein investigated cohort 14 and others, 30 , 31 been found to be an auspicious prognostic factor. It should however be pointed out that the herein described inter-correlations between different subsets of immune cells merely reflect their co-localization in selected tumour regions.…”
Section: Discussionmentioning
confidence: 59%
“…Such a good prognostic value of Tregs in head and neck cancer has subsequently been confirmed by others [98,99] and extended to additional solid neoplasms including colorectal carcinoma [100,101] and bladder cancer [102]. In some tumor types including hepatocellular carcinoma and breast cancer, high levels of intratumoral Tregs have been clearly associated with bad prognosis, whereas in other types such as colorectal cancer, head and neck carcinoma and lymphoma, robust tumor infiltration by Tregs frequently correlates with improved disease outcome [103,104].…”
Section: Clinical Significance Of Intratumoral Tregsmentioning
confidence: 78%
“…In contrast, Ling et al [98] found no significant difference in Treg density between advanced and earlystage disease, but did not evaluate the association with patient survival. Salama et al [99] showed that a high density of FOXP3 + Tregs in CRC was associated with an improved survival and had a stronger prognostic significance than CD8 + and CD45RO + memory T lymphocytes in CRC. In contrast, a high density of FOXP3 + Tregs in normal colon of CRC patients was associated with worse prognosis.…”
Section: Foxp3 + Tregs Prognosis and Msi-statusmentioning
confidence: 99%